A Collaborative Approach to the Recruitment and Retention of Internationally Educated Nurses Into Rural Communities - Catherine Baxter (Nursing Leadership, 2025)
Rural communities across Canada are experiencing a shortage of registered nurses (RNs). Internationally educated nurses (IENs) make up an important component of the nursing workforce; however, the recruitment and retention of IENs in rural areas can be challenging. This article will discuss a collaborative rural IEN RN pilot that centred on a partnership between Manitoba Health, two regional health authorities, the College of Registered Nurses of Manitoba and Red River College Polytechnic. The purpose of the pilot was to recruit IENs who were living in Canada, seeking licensure as RNs and were interested in living and working in rural Manitoba.
Keywords: internationally educated nurses; rural nursing workforce; recruitment and retention